Terminator 3 rise of the machines - Kassar, Mario; Brancato, John.; Ferris, Michael; Mostow, Jonathan; Schwarzenegger, Arnold; Stahl, Nick, 1979-; Danes, Claire, 1979-; Loken, Kristanna; Andrews, David, 1952-; Famiglietti, Mark.; Boen, Earl.; Harris, Moira; et al. (Burbank, CA : Warner Home Video, 2003)
John Connor is a 20-something living on the streets as a common laborer. His mother has since died, and their earlier efforts did not stop the creation of SkyNet artificial intelligence network. As he will still become the leader of the human resistance, Connor is once again targeted by a Terminator sent from the future by SkyNet. This new Terminator, T-X, is a female and is more powerful than any of her predecessors. To protect Connor, the human resistance sends a new T-101 back from the future.
DVD, Region 1 encoding, 5.1 Dolby surround.
English or French dialogue, French or Spanish subtitles; Closed-captioned.
Arnold Schwarzenegger, Nick Stahl, Claire Danes, Kristanna Loken, David Andrews, Mark Famiglietti, Earl Boen, Moira Harris, Chopper Bernet.
Producers, Mario F. Kassar, Andrew G. Vajna, Joel B. Michaels; director, Jonathan Mostow; screenplay, John Brancato, Michael Ferris; director of photography, Don Burgess; animator, C. Michael Easton; editor, Nicolas De Toth, Neil Travis; original music, Marco Beltrami; costume designer, April Ferry; production designer, Jeff Mann; visual effects supervisor, Don Lee; special effects, Robert DeVine.
MPAA rating: R; for strong sci-fi violence and action, and for language and brief nudity.
Special features: commentary by Arnold Schwarzenegger, director Jonathan Mostow, Nick Stahl, Claire Danes, Kristanna Loken; introduction by Arnold Schwarzenegger; revealing new footage - creation of the original Terminator machine; Visual Effects Lab: 4 FX vignettes; SkyNet Database: bio profiles of characters including TX- Advances prototype, Hunter Killer Units and John Connor; Terminator timeline; terminal flaws: gag reel; storyboard gallery; dressed to kill: costume and production gallery.
Keywords: Cyborgs -- Drama; Artificial intelligence -- Drama; Feature films; Science fiction films; Video recordings for the hearing impaired